Simulating the hot dip galvanizing process of high mast illumination poles. Part II: Effects of geometrical properties and galvanizing practices. (August 2019) - Nasouri, Reza; Nguyen, Kien; Montoya, Arturo; Matamoros, Adolfo; Bennett, Caroline; Li, Jian
Abstract: Cracks that develop during galvanization of High Mast Illumination Poles (HMIPs), often at the pole-to-base plate connection, are an important concern to US fabricators and highway officials. If they are not detected during fabrication and are allowed to propagate during service, these cracks can pose a significant risk to the public due to the ubiquitous presence of HMIPs in close proximity to roads and highways. Economic losses caused by these cracks include the cost of detailed inspections to ascertain their presence and direct losses associated with discarded poles or repair of cracks that manifest while in service. Modifications to the design of HMIPs and/or the galvanization process to reduce the likelihood of galvanization cracks reduce economic loses, decrease fabrication costs, and improve public safety. This paper presents a parametric study evaluating the effects of geometric configuration and galvanization practices on thermally-induced stress/strain demands during the galvanization of HMIPs. Simulations were performed for poles with standard pole-to-base plate connection details adopted by the Texas DOT. Geometric parameters evaluated in the study included base plate-to-pole thickness ratio, pole shaft geometric shape, and bend radius. Galvanizing practice variables included dwell time, speed and angle of dipping, and cross-section orientation. Simulations were conducted using the commercial software Abaqus, following the methodology validated in a companion paper. In models having the same pole thickness, thermally-induced stresses and strains at critical locations increased with base plate-to-pole thickness ratio. In models with the same base plate thickness, stress and strain demands varied inversely proportional to pole thickness. Stress and strain demands were found to be lower for poles having circular shape than for multi-sided poles, and increases in bend radius led to reductions in localized strain demands. Dwell time was found to have a negligible effect on stress and strain demands, while increased dipping speed and dipping angle resulted in decreased stress and strain demands during galvanizing. Highlights: A numerical parametric study was conducted to study galvanization cracks in HMIPs. The contribution of shape and galvanizing parameters to weld-toe cracks was evaluated. Base plate-to pole thickness ratio was found to play a key role on crack formation. Circular poles exhibited the lowest stress/strain demands during galvanizing. Reducing dipping time and increasing dipping angles reduced plastic deformations.